Modern Work Structure in Consulting - A Guide for Management Consultants to Address Their Clients’ Changing Work Structure - Christensen, Lina (Digital Repository of Theses, 2023)
The purpose of this research is to provide a guide for how management consultants should engage with their clients as companies are redefining their future operations with remote and in person work. This research will utilize existing employee engagement studies and business psychology literature, as well as a qualitative analysis of interviews with 25 Accenture consultants from 5 different career levels. While existing research about employees’ expectations about their work structure is mapped to the psychological benefits and draw backs of these structures, there is limited research about the effects of these on third party contractors like management consultants. This research focuses on addressing that missing piece.